If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1a + ax + -1x = 0 Solving 1 + -1a + ax + -1x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1a + ax + -1 + -1x = 0 + -1 Reorder the terms: 1 + -1 + -1a + ax + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1a + ax + -1x = 0 + -1 -1a + ax + -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1a + ax + -1x = -1 Add 'x' to each side of the equation. -1a + ax + -1x + x = -1 + x Combine like terms: -1x + x = 0 -1a + ax + 0 = -1 + x -1a + ax = -1 + x Reorder the terms: 1 + -1a + ax + -1x = -1 + x + 1 + -1x Reorder the terms: 1 + -1a + ax + -1x = -1 + 1 + x + -1x Combine like terms: -1 + 1 = 0 1 + -1a + ax + -1x = 0 + x + -1x 1 + -1a + ax + -1x = x + -1x Combine like terms: x + -1x = 0 1 + -1a + ax + -1x = 0 The solution to this equation could not be determined.
| 1-ax+ax-x= | | 13x+9x-6y=0 | | 4(+6x)=32 | | 2x-0(2+3)=x | | x²-2x+1=0 | | x/2-9=14 | | 4X=25+X | | 3(1-2y)=27 | | 15+x=45 | | v=bh(h) | | 0.12-0.01(x+2)=-0.03(2-x) | | 8x+13=-3 | | -2x+x=3 | | 12x-4y=13 | | 4(8+5x)=92 | | 9h+10=8h | | m-7=28 | | 3y=10y+3 | | 66x+22=10 | | -x+π=-1 | | y=27x-x^2 | | -6x=78 | | -2+4p=3p | | 3x+3-2=2x+3 | | 8+12x=3(4x+3) | | 3s=4s+10 | | 4q+9=20 | | 15-(-3x)-8x-(-10)= | | 5x+20=2-x | | -28c^2+7=0 | | 10a^2+21ab-10b^2=(2a+5b) | | -4(-7-8n)=2(11+12n)+2n |